Neurochemical supplementation in patients with depressed levels of participation after brain tumor surgery: Rationale and preliminary results. (January 2020) - Briggs, Robert G.; Ahsan, Syed A.; Conner, Andrew K.; Nix, Cameron E.; Jacobs, Christina C.; Jones, Ryan G.; Sheets, John R.; Palejwala, Ali H.; Chendeb, Kassem; Sughrue, Michael E.
Highlights: 101 patients demonstrated an inability to participate in neurorehabilitation (ITPR). 86 of these cases were treated with methylphenidate and levodopa/carbidopa. 47/86 patients showed improvement in their ability to participate in rehabilitation. 58/86 patients were living independently or at least interactive at follow-up exam. 4/86 patients showed elevated blood pressure when receiving neurostimulant therapy. Abstract: A unique challenge in some brain tumor patients is the fact that tumors arising in certain areas of the brain involve the neural structures of consciousness or alertness, limiting the patient's ability to participate in rehabilitation following surgery. A critical question is whether neurostimulant therapy can help patients participate in rehabilitation efforts. We performed a retrospective review of all patients undergoing brain tumor surgery by the senior author from 2012 to 2018. We limited this study to patients with tumors occupying critical structures related to consciousness, alertness, and motor initiation. A combination of methylphenidate and levodopa/carbidopa was used to monitor the progress of patients through neurorehabilitation efforts. We identified 101 patients who experienced an inability to participate in rehabilitation (ITPR) in the post-operative period. Of these, 86 patients (85%) were treated with methylphenidate and levodopa/carbidopa. Cases of ITPR were related to dysfunction of the brainstem (12/86 cases, 14%), thalamus (17/86 cases, 20%), hypothalamus (14/86 cases, 16%), basal ganglia (13/86 cases, 15%), and medial frontal lobe (30/86 cases, 35%). Of the 86 individuals treated, 47/86 patients (55%) showed early improvement in their ability to participate with rehabilitation. At three month follow-up, 58/86 patients (67%) had returned to living independently or were at least interactive and cooperative during follow-up examination. This feasibility report suggests that combined therapy with methylphenidate and levodopa/carbidopa may help patients participate in neurorehabilitation efforts in the immediate post-operative period following brain tumor surgery. Randomized, controlled clinical trials are needed to explore this concept more thoroughly.